Spanish Literature : A Very Short Introduction - Labanyi, Jo (Oxford Oxford University Press, 2010)
This Very Short Introduction introduces the ways in which Spanish literature has been read, in and outside Spain, explaining misconceptions, outlining the insights of recent scholarship, and suggesting new readings. It explores the relationship between Spanish literature and modernity and issues of gender and sexuality.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Spanish Literature -- Literature - Spanish